STRUKTUR AKTANSIAL DAN FUNGSI CERITA RAKYAT DALAM TRADISI BARERE’AN SUKU DAYAK RUUK KAPUAS HULU - Fajar Bahari; Chairil Effendy; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis research was motivated by the desire of researchers to introduce the Barere’an oral literature tradition of the Kapuas Hulu Dayak Ruuk community by reviewing the actans structure and function of folklore in it, Bintang Talu, Siring Bunyo dana Kalang Ating, and Amajik. The method used in this research is descriptive method. The form of this study is qualitative. The approach used in this study is a structural approach. The data source of this research is folklore in the Barere’an tradition, namely Bintang Talu, Siring Bunyo Kalangdana Kalang Ating, and Amajik and the research data is in the form of quotations. Data collection techniques used in this study are direct observation techniques. Based on the research conducted, there were found 3 actans structures in the Bintang Talu story, 2 actans structures in the story ofSiring BunyodanaKalang Ating, and 2 actans structures which were in the Amajik story. Each folklore has 4 functions according to the theory of Wiliam R. Bascom. The implementation of learning research is realized by making the learning design of the 2013 Class X curriculum in high schoolKeywords: folklore function, Kapuas Hulu, Barere’an actans structure